Novel advances in biotransformation and bioactivation research – 2020 year in review. (3rd July 2021) - Khojasteh, S. Cyrus; Argikar, Upendra A.; Driscoll, James P.; Heck, Carley J. S.; King, Lloyd; Jackson, Klarissa D.; Jian, Wenying; Kalgutkar, Amit S.; Miller, Grover P.; Kramlinger, Valerie; Rietjens, Ivonne M. C. M.; Teitelbaum, Aaron M.; et al.
Abstract: This annual review is the sixth of its kind since 2016 (see references). Our objective is to explore and share articles which we deem influential and significant in the field of biotransformation and bioactivation. These fields are constantly evolving with new molecular structures and discoveries of corresponding pathways for metabolism that impact relevant drug development with respect to efficacy and safety. Based on the selected articles, we created three sections: (1) drug design, (2) metabolites and drug metabolizing enzymes, and (3) bioactivation and safety (Table 1 ). Unlike in years past, more biotransformation experts have joined and contributed to this effort while striving to maintain a balance of authors from academic and industry settings.